Comparison of generic and subject-specific models for simulation of pulmonary perfusion and forced expiration - Hedges, Kerry L.; Clark, Alys R.; Tawhai, Merryn H. (Interface focus, 2015)
The goal of translating multiscale model analysis of pulmonary function into population studies is challenging because of the need to derive a geometric model for each subject. This could be addressed by using a generic model with appropriate customization to subject-specific data. Here, we present a quantitative comparison of simulating two fundamental behaviours of the lung—its haemodynamic response to vascular occlusion, and the forced expiration in 1 s (FEV1) following bronchoconstriction—in subject-specific and generic models. When the subjects are considered as a group, there is no significant difference between predictions of mean pulmonary artery pressure (mPAP), pulmonary vascular resistance or forced expiration; however, significant differences are apparent in the prediction of arterial oxygen, for both baseline and post-occlusion. Despite the apparent consistency of the generic and subject-specific models, a third of subjects had generic model under-prediction of the increase in mPAP following occlusion, and half had the decrease in arterial oxygen over-predicted; two subjects had considerable differences in the percentage reduction of FEV1 following bronchoconstriction. The generic model approach can be useful for physiologically directed studies but is not appropriate for simulating pathophysiological function that is strongly dependent on interaction with lung structure.